Secondary Structure and Membrane Topology of the Full-Length Dengue Virus NS4B in Micelles - Li, Yan (2017)
Dengue virus nonstructural protein 4B (NS4B) is a membrane protein consisting of 248 residues with a crucial role in virus replication and interference with the host innate immunity. The dengue virus serotype 3 NS4B was reconstituted into lyso-myristoyl phosphatidylglycerol (LMPG) micelles. Backbone resonance assignment of NS4B was obtained using conventional solution NMR experiments. Further studies suggested that NS4B contained eleven helices and six of them form five potential transmembrane regions. This study provides atomic level information for an important drug target to control flavivirus infections.